FAKTOR-FAKTOR YANG DAPAT MEMPENGARUHI CASH HOLDING PERIODE 2017-2019 - Shannon Hidajat; Linda Santioso (Jurnal Paradigma Akuntansi, 2022)
The purpose of this research is to examine the effects of cash flow, leverage, firm size, cash flow volatility and net working capital that can influence corporate cash holding of manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. This research used purposive sampling method and included 82 samples of manufacturing companies. Statistical Product and Service Solution Version 21 (SPSS Program) was used in this research to process data. The results in this study show that cash flow and cash flow volatility has a positive significant effect towards cash holding and leverage has negative significant towards cash holding, while firm size and net working capital was found to have no effect towards cash holding.